PERSEPSI KENYAMANAN DAN HARGA TERHADAP MINAT PENGGUNAAN JASA TRANSPORTASI ANGKUTAN UMUM KOTA DI KABUPATEN PURWAKARTA - Ade Nurhayati (Eqien - Jurnal Ekonomi dan Bisnis, 2020)
Reduced interest in the use of city public transport services because there are still many public transport facilities that do not attach importance to the convenience of service users and the absence of alternative tariff options for long distance or short distance, so service users choose to use other transportation services that can answer their needs, such as transportation online that already exists in Purwakarta today. In this case the author is very interested in conducting research, with the title "The Influence of Perceptions of Comfort and Price Against Interest in the Use of City Public Transportation Transportation Services in Purwakarta District". The purpose of this study was to determine the effect of perceived comfort and price on the interest in using the City Public Transport Service in Purwakarta Regency. In this study respondents were users of public transportation services in Purwakarta using sampling techniques called Non-Probability Sampling. The research method used is descriptive qualitative method, which is a method that is done by collecting, presenting and analyzing data that gives a clear enough picture of the object under study. This study uses a multiple linear regression analysis model with the help of IBM SPSS 21 program. Hypothesis This study shows that the variables of perceived comfort and price have a positive and significant effect on the interest in using public transportation services in the city of Purwakarta.